Adaptation of the Beck Hopelessness Scale as a suicide risk screening tool among Nigerian patients with schizophrenia. (2nd January 2018) - Aloba, Olutayo; Esan, Olufemi; Alimi, Taiwo
Abstract: Objectives: We examined the adaptation of the Beck Hopelessness Scale (BHS) as a subjective suicide risk assessment tool in detecting Nigerian patients with schizophrenia who are at a high risk of suicide. Methods: Schizophrenia patients (211) completed the BHS in addition to a sociodemographic questionnaire. They were objectively interviewed with the suicidality module of the Mini International Neuropsychiatric Interview (MINI) as the 'gold standard', against which the criterion validity of the BHS was examined. Results: The receiver operating characteristics (ROC) curve of the 20-item BHS scale at a total cut-off score of 9 (sensitivity 0.889, specificity 0.916) against the patients' MINI Suicidality Module risk categorisation had an Area Under the Curve (AUC) of 0.96 (95% CI: 0.928–0.987), while, the four-item BHS scale demonstrated a ROC curve with an AUC of 0.92 (95% CI: 0.868–0.966) at a cut-off score of 1 (sensitivity 1.000, specificity 0.832). Conclusions: The BHS has proven to be valid in terms of its sensitivity and specificity in the identification of the high suicidal risk Nigerian schizophrenia outpatients.